Inflammatory biomarker-based clinical practice in patients with pneumonia: A systematic review of randomized controlled trials - Dimitropoulos Dimitrios; Karmpadakis Michalis; Paraskevas Themistoklis; Michailides Christos; Lagadinou Maria; Platanaki Christina; Pierrakos Charalampos; Velissaris Dimitrios (Sciendo, 2024)
Objectives: Biomarker-based clinical practice is currently gaining ground and increasingly affects decision making. A variety of biomarkers have been studied through the years and some of them have already an established role in modern medicine, such as procalcitonin (PCT) which has been proposed to reduce antibiotic exposure. We purposed to systematically review all biomarkers examined for guiding the clinical practice in patients with pneumonia.